Dissection indices and their distribution over Mongolia - Bumtsend, Bayanjargal; Munkhtur, Purevsuren; Enkhjargal, Odbaatar (Proceedings of the Mongolian Academy of Sciences, 2023)
The main objective of this study was to create much more accurate maps of the ‘dissection depth’ and ‘dissection density’ in Mongolia, considering both the vertical and horizontal directions. To achieve this, two digital evetation models (DEMs) were used: the MERIT DEM with a spatial resolution of 90 meters and the ASTER DEM with a resolution of 30 meters. Some adjustments were made to rectify errors in relatively flat areas. The entire territory of Mongolia was selected as the study area, resulting in the creation of 2,865,000 grids with a resolution of 1 km. For each grid, the minimum and maximum values, as well as the length of dissection, were estimated. Finally, an interpolation method was used for mapping the depth and density of the dissection. The utilization of digital elevation models in the dissection map has exposed certain inaccuracies in flat areas. Consequently, the MERIT DEM has been selected as the favored alternative. Furthermore, this study emphasizes the disparities between the dissection depth map and the relative elevation map, as both play a vital role in comprehending and applying the concept of dissection depth. The maps of the dissection density and depth have proven to be highly valuable in the field of geomorphological and landscape research, as well as in the classification of origin groups and typological classification.